Applications for the management of Attention Deficit Hyperactivity Disorder: a systematic review - Hosseinnia, Maede; Pirzadeh, Asiyeh; Nazari, Abouzar; Heidari, Zahra (Frontiers in Public Health, 2025)
BackgroundVarious interventions are available for managing Attention Deficit Hyperactivity Disorder (ADHD), including educational strategies and training programs. Recently, there has been a notable increase in the use of programs and apps as innovative tools to assist with ADHD management. This study aims to provide insights into the possibility of app-based therapies as a supplemental tool for ADHD care by analyzing the indicated advantages and supporting data.MethodsThis systematic review was conducted until May 4, 2024, in several electronic databases, PubMed, MEDLINE, Scopus, Web of Science, and the Cochrane Central Register of Controlled Trials. In addition, we conducted a comprehensive search for relevant grey literature. The studies included trials, quasi-experimental studies, and observational studies on using apps to control ADHD. This includes studies that were published in English.ResultsA review of 14 studies investigated the effectiveness of ADHD applications. Several applications monitored symptoms and enhanced cognitive function. Healthcare providers enhanced communication using the AKL-X01 app to monitor and record symptoms. The FOCUS ADHD app was well accepted but did not improve treatment compliance. The Sensory Diet App, known for its user-friendly interface, effectively alleviated symptoms associated with ADHD. BRUSH DJ enhanced dental hygiene and concentration on toothbrushing.ConclusionApps can potentially be adjunctive instruments for treating ADHD. Nevertheless, further study is required to validate their effectiveness over a long period and enhance their incorporation into complete treatment strategies for ADHD.Systematic review registrationidentifier CRD42024523528 (PROSPERO).